THE INFLUENCE OF GEODYNAMIC FACTORS ON THE POSTSEDIMENTARY LITHOGENESIS OF JURASSIC TERRIGENOUS COMPLEXES OF THE CAUCASUS (SOUTHERN DAGESTAN) - Simanovich I.M.; Golovin D.I.; Bujakaite M.I.; Vinogradov V.I.; Sakharov B.A.; Sokolova A.L.; Pokrovskaya E.V.; Matsapulin V.U. (My University, 2004)
The influence of geodynamic factors on the postsedimentary lithogenesis of terrigenous sequences during the replacement of the passive continental-margin regime to the active regime is considered with the Toarcian–Aalenian complexes of southern Dagestan as an example. It has been established that clayey rocks were lithified under conditions of subsidence lithogenesis, whereas the orogenic catagenesis of sandy rocks was related to stress initiated by the initial (amagmatic) subduction phase. The Kbler index has been used to reveal the postsedimentary zonality that is consistent with the intensity of folding and cleavage. The metagenesis zone fits the cleavage zone. The Rb–Sr and K–Ar datings of clayey rocks from the metagenesis zone yielded 180–190 Ma that can be interpreted as the timing of the maximal manifestation of postsedimentary lithogenesis.
Keywords: Jurassic; Mesozoic::Jurassic; Мезозой::Юрская